Cognitive neuroscience, reading literary texts, and emotional education - Giuseppe Longo (Pensa MultiMedia, 2015)
The three major jobs of the reading brain are recognizing patterns, planning strategy, and feeling (Wolf, 2007). When we read fiction, we expect to experience emotion (Johnson Laird, Oatley, 2008), and literature is probably the first home of the emotional intelligences (Mayer, Salovey, 1997). According to these assumptions, this paper examines the connection between cognitive neurosciences and reading literature to verify whether the literary text can be used in the field of emotional education. The brain-based interaction between text and reader as an "immersed experiencer" (Zwaan, 2004), and therefore also the processes of comprehension will be synthetically analyzed in the light of recent neuroimaging research. How emotion, metaphor, and mental imagery are connected within the process of interpretation will be particularly investigated. The cognitive approach of embodiment and the emotional state of empathy are also involved in the analysis, because their neurocognitive role allows us to explain why the literary text can become a useful tool to enhance students' emotional competence.